RANCANG BANGUN ANTENA MICROSTRIP SEBAGAI PENGUAT SINYAL WIFI DAN JARINGAN 4G LTE PADA FREKUENSI 1800 MHZ - Angga Permana; Nifty Fath (MAESTRO, 2021)
This final project aims to design a microstrip antenna that can be applied to amplify WiFi (Wireless Fidelity) signals and 4G LTE networks with a frequency of 1800 MHz. The design of the microstrip antenna was made because of the large number of users of the Wifi network and the lack of BTS on the 4G network with the Indosat provider, so that the quality of the network decreases, so a tool is needed as a WIFI and 4G signal amplifier using a rectangular microstrip antenna. The material used to relax this antenna is FR-4 Epoxy (double layer) which has a dielectric constant (єr) = 4.3 with a thickness dimension (h) of 2.5 mm and a copper thickness (t) of 0.035 mm. To get the antenna design, it is necessary to calculate each antenna parameter, so that it can design and simulate microstrip antennas using ANSYS HFSS software. Based on the research that has been done, the antenna design results with the formula have a patch length L = 40,442 mm, groundplane length Lg = 50,042 mm, main supply length Lf = 16.25 mm, patch width W = 51.19 mm, groundplane width Wg = 60, 79 mm, and the width of the main supply line Wf = 1.33mm. From the simulation results of the ANSYS HFSS software, the value of VSWR = 1.382, Gain = 5.128dB, after getting the antenna dimension values and performing simulations on the ANSYS HFSS software, then fabrication and looking for antenna parameters using the Spectrum Analyzer at the Radar LAB, University of Indonesia, obtained the results from the test. research value of VSWR = 1.17, Gain 22.9dB. After it is stated according to the specifications for the signal amplifier on the antenna that has been fabricated, then measurements are made before and after using the antenna on the Wireshark software. The results of the comparison of QoS (Quality of Service) measurements in the morning, afternoon and evening after using a microstrip antenna on a WIFI network. Throughput = 1472.22bps, Packet Loss = 0%, Delay = 6.4ms, Jitter = 0.0153ms. For the value on the LTE network Throughput = 1359.24bps, Packet Loss = 0.103%, Delay = 10.1ms, Jitter = 0.01958ms.